Reverse engineering and its impact on reducing production costs and improving quality - Mohammed Jaber Kadhim, Yousif Mashkoor Kadhim, Adnan Askar Alwan, (Opción, 2019)
The aim of the study is to investigate reverse engineering and its impact on reducing production costs and improving quality. In reverse engineering methodology the vital steps concerned, are features of mathematical models and connected surface representations, breaking and surface fitting of straightforward and free-form shapes, and making correct CAD models. As a result, the first nerve fiber arm spacing may operate on the cooling rate that successively depends on the casting method. In conclusion, the two primary objectives of applying reverse engineering in producing are to reinvent a part for market competition or for part restoration.